Fulfilling psychological needs predicts less sleep disruption and worry while awaiting uncertain news. (4th April 2019) - Howell, Jennifer L.; Sweeny, Kate
Abstract: Research on self‐determination theory suggests that people have fundamental needs to feel autonomous, competent, and socially connected and that fulfilling these needs is critical for well‐being. In the present study, we examined whether fulfilling psychological needs is associated with physical and psychological well‐being—specifically sleep disruption and worry, two key indicators of well‐being during waiting periods—while managing the unique stress of awaiting uncertain news. In a study of law graduates during the 4 months while they awaited their California bar exam (the exam one is required to pass before practicing law) results, personal increases in need fulfilment related to temporally congruent reductions in sleep disruption and worry. In addition, those whose needs were most fulfilled during the waiting period responded less negatively to failing the bar exam. The picture for need frustration was mixed; only autonomy frustration was associated with concurrent increases in worry, although those whose needs were more frustrated in general also experienced greater worry and sleep disruption on average. On the whole, our findings suggest that self‐determination theory needs may be a fruitful target for interventions that can protect well‐being while people wait and even once their uncertainty is resolved.